Moderating Effect of Buyer-Supplier Trust on the Relationship between Outsourced Formal Contracts and Supplier Delivery Performance: An Empirical Study of Public Sector Procurement - Ahimbisibwe, Arthur; Nangoli, Sudi; Tusiime, Wilson (International journal of business and social science, 2012)
This study examines the moderating effect of buyer-supplier trust on the relationship between outsourced formal contracts and supplier delivery performance in the domain of public sector procurement. In so doing, we extend the paradigm that formal contracts and relational governance mechanism function as complements rather than substitutes. Using a cross sectional data from a survey of 612 staff that are involved in managing outsourced contracts in Ugandan public sector, Structural Equation Modelling results support 10 of the 14 hypotheses thus, demonstrating the fundamental preposition of complementarity between formal contracts and relational governance mechanisms. Also, findings revealed that well-structured outsourced formal contracts have a significant positive influence on buyer-supplier trust and supplier delivery performance.However, the path coefficient for the interactioneffect between change characteristics and buyer-supplier trust was initially hypothesised to positively influence supplier delivery performance but did not.The use of case studies and additional surveys in future research might help to explain this phenomenon. Although the two constructs of buyer-supplier trust and supplier opportunism are robust and sufficiently represent the relational aspects, the multidimensional nature of relational practises can be investigated further. This study has managerial and policy implications that are also discussed in this paper.
Keywords: Outsourced formal contracts; Relational governance; Supplier delivery; Performance